PAI and Technology Collaboration Towards Interactive and Meaningful Learning - Wahida Mursalim; Ihsan Kamil; Ahmad Syahid; Erniati Erniati; Nasrul Nasrul (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Islamic Religious Education (PAI) plays an important role in Indonesia's educational curriculum, particularly in shaping students' character and moral values. With approximately 90% of schools in Indonesia teaching PAI, the integration of information and communication technology (ICT) has become increasingly relevant, especially following the rise of online learning platforms during the COVID-19 pandemic. Collaboration between PAI and technology is expected to create interactive and meaningful learning experiences, enhancing student engagement and motivation. This study employs a qualitative approach with a case study design to explore the effectiveness of technology use in PAI learning across several schools. Data were collected through interviews, observations, and document analysis, and analyzed using a thematic analysis approach. The findings indicate that technology can increase student engagement by up to 30% and learning motivation by up to 40%, with interactive learning models such as the flipped classroom and project-based learning proving to be effective methods. However, challenges such as technological accessibility and teacher readiness need to be addressed to maximize the potential of this collaboration.